Calidad físico química y rendimiento del jabón de tocador a partir de aceites residuales provenientes de chiflerías - Cedeño Cevallos, Julio Cesar (2023)
The objective of the research was to determine the physical-chemical quality and performance of toilet soap made from residual oils from five chiflerías in different cantons Manabí province: Chone, Tosagua, Calceta, Bahía and Junín, as treatments, incorporating the coffee grounds to give it an exfoliating effect. A completely randomized design was applied, with three repetitions. Analysis of pH, foam level, yield, percentage of moisture content and volatile matter and only the percentage of total fat matter and sensory evaluation were carried out in treatments. All treatments comply with the INEN 841 standard by not exceeding the maximum allowed in pH and percentage of moisture content and volatile matter, in foam levels T1 (Chone) and T5 (Calceta) they have the highest values, over 70 cm3. In performance according to the Kruskal Wallis test there were significant differences (p<0.05), demonstrating that the T4 treatment belonging to Junín obtained a higher performance with 93.41%, compared to the rest that were above 90%. In the sensory analysis, the judges determined that there are significant differences (Sig. <0.05) for the variables of color, odor, exfoliant and foam, while the null hypothesis is retained for the texture variable. It is concluded that all treatments are suitable for the production of toilet soap, both in terms of physical, chemical and sensory characteristics.